History of chemistry: a theoretical study on the pile of Alessandro Volta (Research, Society and Development, 2020)
This article aims to reveal the importance of the work of the Italian physicist and chemist Alessandro Volta, in the 18th century, the voltaic cell. Also aiming at the relevance of this invention in the teaching of chemistry in high school, more specifically in the study of batteries, in which there is a gap in relation to this subject, often unnoticed and without crediting the real importance, neither to the content studied, nor to scientists involved in the discoveries. These are vitally notable so that the student can feel comfortable and understand that scientific discoveries occur with successions of works and research. The research also calls for attention to the scientific and technological advance of batteries over the centuries after their invention, for the scientists responsible for these advances; and yet, it alludes to the environmental impacts caused by the rampant consumption of electronic devices that use some type of battery since the first devices that used this technology for their operation.